THE PEDAGOGY AS A DISCIPLINE FOR PREPARING TEACHERS - Vasiliauskas, Romanas (Acta Paedagogica Vilnensia, 2008)
The development of education and preparation of teachers for theory and practice based profesional activity, the relationship between the subject discipline and professional training in Lithuania in the previous century are analysed in the article. In historical view education had developed as both the theory and practice of teaching and had been called by different terms – pedagogy theory and pedology practice of education.To the very end of the 19th century priority was given to preparing teachers for primary schools inteacher training seminaries. In the period from the beggining of 20th century pedagogy became as a subject taught at university. Pedagogy as a specific focus of study appeared since 1922 in Kaunas University. The first pioneers in founding pedagogy as a university subject were well-known Lithuanian philosophers S. Salkauskis and A. Maceina in whose works teacher education and the models of teaching were based on the philosophical conception of man and on the nature of research concerning education.Pedagogy as a university subject was divided into three parts: general pedagogy, theory of upbringing and didactics which focussed on training processes. In S. Šalkauskis view, the core of education is the philosophy of education which fulfiled two main functions – methodological and world view.As it is discusesed in the article, didactics became the main subject representing teacher education in the soviet and postsoviet periods. The postsoviet period in Lithuanian didactics became a distinct component of teacher education and education theory.
Keywords: pedagogy; didactics; general didactics; subject didactics; teacher training; theory and practice of education